ESTIMASI PERUBAHAN TUTUPAN LAHAN DENGAN MENGGUNAKAN NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) DI KABUPATEN KLUNGKUNG PROVINSI BALI - Aryastana, Putu; Widya, I Gusti Ngurah Agung; DAna, Gde Wikan Pradnya; Suyasa, I Putu Suta; Tamara, Wayan Wahyu Adnyana (Jurnal Teknik Gradien, 2023)
The development of development in urban areas will also have an impact on the land cover area. Efforts that can be made to determine urban development are by looking at land cover information through land cover maps. Land cover data can provide information in studying climate change and understanding the relationship between human activities and climate change. The method used is descriptive with interpretation of Landsat 8 imagery, using a Geographic Information System (GIS). Normalized Diffrence Vegetation Index (NDVI) is a calculation on an image that is used to determine the level of greenery as the initial division of vegetation and land cover areas. Klungkung Regency in the last five years continues to experience changes. The area of paddy fields in Klungkung Regency in the past five years tends to decrease. In 2013 the area of paddy fields was 3,843 Ha, reduced to 3,779 Ha in 2017. Based on the results of Landsat 8 satellite imagery, from 2016 to 2021 there was a decrease in the area of vegetation density by 35.11 km2 or 11.39% while the area of residential land cover increased by 29.98 km2 or 9.73%.